O poder médico de “penetrar” e o poder jurídico de “infamar” : um crime de defloramento em Cuiabá (1920-1940) - Moreira, Mayara Laet (2015)
The discursive frame of this research has as starting point the narrative of Aldair França‟s experience, whose trajectory caused disorder, turmoil and excitement in the city of Cuiaba in the 1930s. We focused on, from those events point of view, the invisible networks entered substantially in the technical procedure process of sexual crime that brought forth this character, as well as the system of truths and discourses of knowledge-power that circulated between the 1920s and 1940. All its context is crossed by a fine line between legal discourse and the medical knowledge, which sought to control her body, her sexuality, discipline her daily practices, her gestures, unravel her secrets and her desires. It is also necessary to highlight the game of halves running through the criminal process from beginning to end, and that gradually adjusted the pieces to one another harvested in the course of this police drama in an attempt to reconstruct the scene of the crime. Finally, we try to give visibility to the event itself which is already causing tension between the State laws and the family institution, in revealing clues about the opening of possible worlds. Caught up in this proposal and inspired by Michel Foucault, we intend to bring forward the subjectivity processes circumscribed in this sex crime case that identified, examined, classified and cataloged this female character.